‘Flash’ Annealing in a Cold-Rolled Low Carbon Steel Alloyed with Cr, Mn, Mo, and Nb: Part I - Continuous Phase Transformations - Schulz-Eglin, B; Castro-Cerda, F (Wiley-VCH Verlag, 2019)
The aim of the present work is to study the microstructure evolution of a cold-rolled low carbon steel alloyed with Cr, Mn, Mo, and Nb during continuous heating. The formation of austenite and its further transformation is examined by means of peak annealing experiments at three different heating rates, followed by quenching. The effect of carbide-forming alloying elements in the kinetics of austenite formation and decomposition is discussed with the aim of DICTRA calculations. Electron Probe Micro Analysis allows the detection of small compositional fluctuations within the microstructure, which are responsible for local changes in the mechanism of austenite formation. It is experimentally demonstrated that the temperature dependence of the austenite fraction is relatively insensitive to the heating rate. It is suggested that carbide-forming alloying elements slow down the kinetics of austenite formation. © 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim